Ocular Impression-Based Scleral Lens With Wavefront-Guided Optics for Visual Improvement in Keratoconus. Issue 11 (28th November 2022) - Gelles, John D.; Cheung, Brian; Akilov, Sarah; Krisa, Sydney; Trieu, Gina; Greenstein, Steven A.; Chung, Daniel; Hersh, Peter S.
Abstract: This case reports on the use of wavefront-guided (wfg) optics on custom ocular impression-based scleral lenses (IBSLs) for visual improvement in a patient with keratoconus (KC). A 28-year-old man with KC, who had previously failed a traditional, diagnostically fit scleral lens (tSL), was fit with IBSLs with traditional optics. Using a system that included a dot matrix on the IBSL and a wavefront aberrometer with pupil and dot registration software, a wfgIBSL was created. When compared with the IBSL, the wfgIBSL reduced the total higher-order root mean square (HORMS) 67% and 64% in the right and left eye, respectively, resulting in a 2-line improvement in best-contact lens visual acuity (BCLVA) for both eyes. This case demonstrates the successful creation and application of a wfgIBSL resulting in a stable lens, a reduction in HORMS, and an improvement in BCLVA, after failure with a diagnostically fit tSL.